Anti-adhesive antimicrobial peptide coating prevents catheter associated infection in a mouse urinary infection model. (February 2017) - Yu, Kai; Lo, Joey C.Y.; Yan, Mei; Yang, Xiaoqiang; Brooks, Donald E.; Hancock, Robert E.W.; Lange, Dirk; Kizhakkedathu, Jayachandran N.
Abstract: Catheter-associated urinary tract infections (CAUTIs) represent one of the most common hospital acquired infections with significant economic consequences and increased patient morbidity. CAUTIs often start with pathogen adhesion and colonization on the catheter surface followed by biofilm formation. Current strategies to prevent CAUTIs are insufficiently effective and antimicrobial coatings based on antimicrobial peptides (AMPs) hold promise in curbing CAUTIs. Here we report an effective surface tethering strategy to prepare AMP coatings on polyurethane (PU), a common biomedical plastic used for catheter manufacture, by using an anti-adhesive hydrophilic polymer coating. An optimized surface active AMP, labeled with cysteine at the C-terminus (RRWRIVVIRVRRC), was used. The coated PU surface was characterized using ATR-FTIR, XPS and atomic force microscopy analyses. The tethered peptides on the PU catheter surface displayed broad spectrum antimicrobial activity and showed long term activity in vitro . The surface coating prevented bacterial adhesion by up to 99.9% for both Gram-positive and -negative bacteria, and inhibited planktonic bacterial growth by up to 70%. In vivo, the coating was tested in a mouse urinary catheter infection model; the AMP-coated PU catheter was able to prevent infection with high efficiency by reducing the bacteria adhesion on catheter surface by more than 4 logs (from 1.2 × 10 6  CFU/mL to 5 × 10 1  CFU/mL) compared to the uncoated catheter surface, and inhibit planktonic bacterial growth in the urine by nearly 3 logs (1.1 × 10 7  CFU/mL to 1.47 × 10 4  CFU/mL). The AMP-brush coating also showed good biocompatibility with bladder epithelial cells and fibroblast cells in cell culture. The new coating might find clinical applications in preventing CAUTIs.